Element variability in lacustrine systems of Terra Nova Bay (Antarctica) and concentration evolution in surface waters. (August 2017) - Zelano, Isabella; Malandrino, Mery; Giacomino, Agnese; Buoso, Sandro; Conca, Eleonora; Sivry, Yann; Benedetti, Marc; Abollino, Ornella
Abstract: Major, minor and trace elements were determined in freshwater of lacustrine systems in Terra Nova Bay, along Victoria Land coast, Antarctica, as well as in algae and mosses. The samples were collected during some of the sampling campaigns between 2007 and 2011 (and the one of 2002) within the framework of the Italian National Program of Research in Antarctica (PNRA). Data were processed with chemometric techniques. Results showed that elements typically considered as potential anthropogenic pollutants (e.g. As, Pb, Zn, Cu and Ni) present a strong correlation with the lithogenic elements (e.g. Al, Si, Fe) in all matrices, suggesting that their origin is connected to natural phenomena. Metal concentrations in vegetation samples are in the same range as previously published data. The obtained results were compared with older literature data (since the early '90s) from the same lacustrine systems, in order to present a historical overview of element concentrations. This approach furnishes important information on surface water evolution as a function of time. A considerable variability was observed in metal concentrations but no clear trend was identified. This suggests that their concentration evolution is hardly correlated to specific natural or anthropic phenomena. No evidence of an increase of concentrations over time was apparent. Our results represent new important data about metal concentrations in lacustrine systems in Antarctica, furnishing ranges of values that can be considered as a reference. These data, therefore, could be used to detect or monitor future local and/or global anthropogenic contaminations. Highlights: Concentrations in lake waters depend on geochemical and geographical features. Potentially toxic and geogenic elements are correlated, suggesting a natural origin. No trend of data concentrations over time since the early 90's was detected.